Harmful Algal Bloom in Iligan Bay, Southern Philippines - Vicente, Helen J; Gaid, Ruth D.; Dejarme, Henry E.; Roa, Elnor C.; Azanza, Rhodora V. (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
We report the first occurrence of harmful algal bloom (HAB) caused by a non-toxic dinoflagellate, Cochlodinium sp. in Philippine waters, particularly, in Kalangahan Pt.-Manticao Pt., Iligan Bay on March 13-18, 2002. Two patches of Cochlodinium sp. bloom, associated with fish kills in Kalangahan Pt.-Mantacao Pt., Iligan Bay, caused localized water discoloration from the usual ocean blue to rusty brown or reddish brown to blackish. The first patch, located near fish-aggregating device (FAD) areas, spanned 2 km wide, while the second patch, located near a fish corral, spanned 500m wide. These patches occupied the water column from surface to 5 m depth, but a thick mat formed at 0.5 m to surface. Patches occupied the water column from surface to 5 m depth, but a thick mat formed at 0.5 m to surface. Patches decreased as the bloom began to decline. The observed dead demersal and pelagic fishes coincided with highest bloom density of 3.1 x 104 to 3.8 x 104 cells ml-1 of Cochlodinium. Dissected gills and stomach contents of fishes killed in HAB-affected areas did not reveal any indication of clogging of gills by Cochlodinium sp. Fishes covered by the “shading effect” of Cochlodinium bloom may have suffered anoxia or asphyxation due to oxygen depletion. No poisoning of people who consumed the dead fishes was reported. Laboratory analyses revealed lower DO values, 2.4 to 0.5 mg L-1from 2400 to 0600Hr; 14N:1P ratio; air-water temperature ranged from 28-29°C; pH 7.89-8.29; and salinity, 33-35°/oo. Favella sp., a tintinnid grazer of dinoflagellate was developing in the area at the termination of the Cochlodinium bloom on March 18.
Keywords: HABs; discoloration; cochlodinium sp; anoxia; asphyxation; fish kill; favella sp